Standards Commonly Used for Microgrids—A Research Project to Develop an Industry Microgrid Standard in Taiwan. Issue 19 (25th November 2016) - Bui, Duong Minh; Lien, Keng-Yu; Chen, Shi-Lin; Cheng, Xiao-Yan; Lin, Ming-Shan
Abstract: This article presents standards commonly used for microgrid technology and practical tests of these standards before developing an industry microgrid standard. Standards of communication networks, Internet security, data and communications security, installation and protection of distributed generators and energy storage devices, electronic power interfaces of distributed energy resources, and interconnection of microgrids to electric power system are analyzed. The practical tests for the above standards are planned to perform at a low-voltage (380-V) AC microgrid test bed built by the Institute of Nuclear Energy Research, Taiwan. Microgrid configurations, installation of distributed generators and energy storage systems, operation conditions of the microgrid, microgrid energy management and control systems, and microgrid protection are mentioned in the proposed standard tests. The main contributions of this article are (i) to review and analyze common standards used for microgrids, (ii) to present research works from Taiwan to develop a microgrid standard for industry applications, and (iii) to propose practical tests of critical standards used for microgrids and how to perform these tests at a real-time low-voltage AC microgrid in Taiwan.